Physician demography in Lebanon 2024: identifying gaps and proposing solutions for sustainable healthcare system - Jana Doghman; Salim Saba; Joseph Bakhach (BMC Health Services Research)
Abstract Background Lebanon continues to experience dramatic changes in its medical demography following the ongoing economic crisis of 2019, including brain drain of physicians across different specialties. This paper assesses the landscape of physicians in Lebanon in 2024 to highlight gaps and propose solutions. Methods A List of registered physicians is obtained from the Lebanese Order of Physicians (LOP) in Beirut and Tripoli. Lists are filtered to remove redundant data, and physicians are sorted based on their specialty and work location. Data on the number of trainee graduates at residency training programs, from 2018 to 2022, is collected from the medical schools in Lebanon. Physician density is calculated using the most recent published data on the number of populations in Lebanon. Results Of the 15,059 physicians registered in the LOP in 2023, 68.7% (10,344) are practicing specialized medicine and 31.3% (4,715) are primary care practitioners. The ratio of residency trained primary care practitioners is 7.11 per 100,000 population, sharply below the recommended ratio; in contrast, the ratio of surgeons is 70 per 100,000 population exceeding recommended ratios. The significant imbalance observed across different specialties is compounded with insufficient assessment of the residency programs to meet the actual needs of the community. Most physicians practice in the Beirut metropolitan area, thus leaving other regions in Lebanon underserved. Conclusion There is an imbalanced distribution of physicians in Lebanon based on represented specialties and practice location. We propose implementation of regulatory measures, post-graduate education programs, and financial incentive strategies to bridge this gap and meet the needs of the Lebanese people.